German Economy Spring 2021 - Recovery ready for second take off - Martin Ademmer; Jens Boysen-Hogrefe; Salomon Fiedler; Dominik Groll; Nils Jannsen; Stefan Kooths; Saskia Meuchelböck (Kiel Institute for the World Economy (IfW), 2021)
The second wave of the Covid-19 pandemic has interrupted the recovery in Germany. GDP is set to decline in the first quarter of this year, after stagnating in the previous quarter. However, with the vaccination campaign progressing, the economic burden of the pandemic will ease and the recovery will continue at a rapid pace. Unlike last year, the economic losses are currently much more concentrated on consumer-related service industries and retail trade. Even though the negative impact on private consumer spending is currently even more severe than at the beginning of the pandemic, the overall economic impact will be much smaller. The main reason is that the export business continues to recover. Moreover, with sustained relief in sight for many companies due to the availability of effective vaccines, there will be no major decline in investment. Overall, GDP is expected to pick up strongly with growth rates of 3.7 percent this year and 4.8 percent next year, following the decline of 4.9 per cent in 2020. The recovery at the labor market will take more time. On average, employment is not yet expected to be higher in 2021 than in 2020; it will only pick up noticeably in 2022. Inflation is expected to rise significantly above 2 percent this year. However, temporary factors will contribute significantly to this increase and therefore the inflation rate is expected to decline again in 2022. Finally, the pandemic is also leaving its mark on public budgets. Due to the pandemic-related additional expenditures and revenue shortfalls, the budget deficit this year will once again be well above 4 percent relative to GDP. In 2022, the deficit will probably decline significantly to 1.3 per cent. The debt level will then be just under 70 per cent again.
Keywords: 330; business cycle forecast; stabilization policy; leading indicators; outlook; Business Cycle Germany; Fiscal Policy & National Budgets; Labor Market